2016
DOI: 10.1002/jor.23253
|View full text |Cite
|
Sign up to set email alerts
|

Nonsurgical treatment and early return to activity leads to improved Achilles tendon fatigue mechanics and functional outcomes during early healing in an animal model

Abstract: Achilles tendon ruptures are common and devastating injuries; however, an optimized treatment and rehabilitation protocol has yet to be defined. Therefore, the objective of this study was to investigate the effects of surgical repair and return to activity on joint function and Achilles tendon properties after 3-weeks of healing. Sprague Dawley rats (N=100) received unilateral blunt transection of their Achilles tendon. Animals were then randomized into repaired or non-repaired treatments, and further randomiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
151
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 57 publications
(157 citation statements)
references
References 48 publications
6
151
0
Order By: Relevance
“…Achilles tendon ruptures are common and devastating injuries in humans [34]. Despite improved knowledge of Achilles tendon pathology, the optimal treatment and the best rehabilitation protocol after an acute rupture remain a matter of controversy in orthopaedic and sports medicine [35].…”
Section: Discussionmentioning
confidence: 99%
“…Achilles tendon ruptures are common and devastating injuries in humans [34]. Despite improved knowledge of Achilles tendon pathology, the optimal treatment and the best rehabilitation protocol after an acute rupture remain a matter of controversy in orthopaedic and sports medicine [35].…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that full loading improves Achilles tendon healing and this has also been shown in other studies (3,9,16,18,19,22,38,42,43). The improvement by mechanical loading is usually evaluated in the early phases of Achilles tendon healing, 1-3 weeks after injury (3,9,16,18,22,27), but later evaluation has also been made (21,43).…”
Section: Comparison With Other Studiesmentioning
confidence: 77%
“…The timing of return to mobilization has been tested by other groups and some suggests that immobilization during the early phase of tendon healing is beneficial for the healing process (22,27). Godbout et al showed that full loading immediately after injury impaired mechanical properties after 3 weeks (27).…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
See 2 more Smart Citations